'Everyone gets a kick': Coach characteristics and approaches to inclusion in an Australian Rules Football program for children. Issue 5 (October 2019) - May, Tamara; Sivaratnam, Carmel; Williams, Katrina; McGillivray, Jane; Whitehouse, Andrew; Rinehart, Nicole J
This study aimed to understand coaches' approaches to including children with disabilities in a community-based Australian rules football program for children. Football coaches for the program, called Auskick, completed an online survey providing qualitative and quantitative information about their experiences of inclusive coaching. Coaches (N = 130) completed the survey over 2016/2017. The average years of coaching experience was 3.3 (range 0–19 years). While 79% of coaches had experienced a child with a disability attending their football centre, only 31% of coaches (56% of paid coaches and 27% of volunteer coaches) had completed disability training. Autism, attention deficit hyperactivity disorder and intellectual disability were the most common types of developmental disabilities, and asthma, vision and hearing problems were the most common physical disabilities of children attending the coaches' centres. Eighty-nine coaches provided examples of inclusive approaches. The most common was having an inclusive attitude, asking the parents for help, making adaptations to suit the child, giving extra time, getting additional help and staff training. Community football coaches frequently work with children who have a broad range of developmental and physical disabilities. Coach disability training is needed to support children with disabilities attending these types of sporting programs in the community.